Intended outcome expands in time - Mukesh Makwana (Nature Portfolio, 2017)
Abstract Intentional agents desire specific outcomes and perform actions to obtain those outcomes. However, whether getting such desired (intended) outcomes change our subjective experience of the duration of that outcome is unknown. Using a temporal bisection task, we investigated the changes in temporal perception of the outcome as a function of whether it was intended or not. Before each trial, participants intended to see one of two possible outcomes but received the intended outcome only in half of the trials. Results showed that intended outcomes were perceived as longer than unintended outcomes. Interestingly, this temporal expansion was present only when the intended outcome appeared after short action-outcome delays (250 ms-Exp 1 and 500 ms-Exp 2), but not when it appeared after long action-outcome delay (1000 ms-Exp 3). The effect was absent when participants did not intend and performed instruction-based action (Exp 4). Finally, Exp 5 (verbal estimation task) revealed that intention induced temporal expansion occurs via altering the gating or switch mechanism and not the pacemaker speed. Results are explained based on intention-induced pre-activation resulting in extended temporal experience. Our study not only suggests inclusion of intention as a potential factor influencing time perception but also indicates a close link between intentional binding and the intention induced temporal expansion of its outcome.